Persistence of potential ST398 MSSA in outpatient settings among US veterans, 2010-2019 - Margaret Carrel; Qianyi Shi; Shinya Hasegawa; Gosia S. Clore; Michael Z. David; Eli N. Perencevich; Matthew Smith; Michihiko Goto (Cambridge University Press, 2023)
Novel ST398 methicillin susceptible Staphylococcus aureus (MSSA) in the United States was first observed in New York City (2004-2007); its diffusion across the country resulted in changing treatment options. Utilizing outpatient antimicrobial susceptibility data from the Veterans Health Administration from 2010 to 2019, the spatiotemporal prevalence of potential ST398 MSSA is documented.